A blockchain based decentralized data security mechanism for the Internet of Things - Ge, Chunpeng; Liu, Zhe; Fang, Liming (Journal of parallel and distributed computing, 2020)
The Internet of Things (IoT) is the core infrastructure of the smart city information system. With the explosive growth of IoT devices, how to securely maintain the important data generated by IoT devices has become an important issue. In the conventional IoT-cloud based infrastructure, the sensitive IoT data was stored in a third cloud service provider. However, in such a manner, the private IoT data may be disclosed by the cloud server since the cloud server knows all the data stored in it. This paper, for the first time, proposes a decentralized secure mechanism based on the blockchain technique to store the important data generated in the IoT system. This mechanism effectively solves the data reliability, security and privacy issues that may be encountered in the conventional IoT-cloud system. Considering the defects of simplified payment verification used by light nodes in blockchain networks, this paper proposes an Unspent Transaction Output (UTXO) verification mechanism based on the RSA accumulator, which makes the computational complexity of light nodes to generate and verify the UTXO proof to be constant. The proposed mechanism not only provides proof of inclusion but also supports efficient proof of exclusion for a lightweight node. Our experiment results indicate that the proposed scheme is practical and efficient. •A decentralized IoT data secure mechanism that effectively solves the data reliability, security and privacy issues that may be encountered in the conventional IoT-cloud system.•A verification mechanism based on the RSA accumulator, which makes the computational complexity of light nodes to generate and verify the UTXO proof to be constant.•Not only provides proof of inclusion but also supports efficient proof of exclusion for a lightweight node.